Low Concordance Between T-Cell Densities in Matched Primary Tumors and Liver Metastases in Microsatellite Stable Colorectal Cancer - Dagenborg, Vegar Johansen; Marshall, Serena Elizabeth; Grzyb, Krzysztof; Fretland, Åsmund Avdem; Lund-Iversen, Marius; Mælandsmo, Gunhild Mari; Ree, Anne Hansen; Edwin, Bjørn; Yaqub, Sheraz; Flatmark, Kjersti (Frontiers in Oncology, 2021)
Background The subtype, density and location of tumor infiltrating T-cells are being explored as prognostic and predictive biomarkers in primary colorectal cancer (pCRC) and colorectal liver metastases (CLM). Very limited data exists comparing findings in pCRC and matched CLM. Patients and methods Fifty-eight patients with available pCRC and matched CLM (57/58 microsatellite stable) were included in this OSLO-COMET substudy. In immunohistochemically stained sections, total (Ttot), helper (TH), cytotoxic (CTL), and regulatory (Treg) T-cells were manually counted in hotspots from the invasive margin (IM), intratumor (IT) and tumor adjacent regions to determine T-cell densities. Results A striking accumulation of T-cells was found in IM of both pCRC and CLM with much lower densities in the IT region, exemplified by Ttot of 2838 versus 340 cells/mm2, respectively, in CLM. The correlation at the individual level between T-cell densities in pCRC and corresponding CLM was poor for all regions and T-cell subtypes; for instance, the correlation coefficient (R2) for IM Ttot was 0.07. The IT TH:CTL and Treg:TH ratios were 2.94 and 0.44, respectively, in pCRC, and 1.84 and 0.24, respectively in CLM. Conclusion The observed accumulation of T-cells in the IM regions of pCRC and CLM with low penetration to the IT regions, combined with high TH:CTL and Treg:TH ratios, point to the presence of an immune suppressive microenvironment. T-cell densities of CLM differed markedly from the matched pCRC, indicating that to evaluate T-cell biomarkers in metastasis, the commonly available pCRC cannot serve as a surrogate for the metastatic tumor.